2000
DOI: 10.1161/01.cir.101.13.1512
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol for Prevention of Restenosis After Directional Coronary Atherectomy

Abstract: on behalf of the EUROCARE study groupBackground-In addition to its known properties as a competitive, nonselective ␤ and ␣-1 receptor blocker, carvedilol directly inhibits vascular myocyte migration and proliferation and exerts antioxidant effects that are considerably greater than those of vitamin E or probucol. This provides the basis for an evaluation of carvedilol for the prevention of coronary restenosis. Methods and Results-In a prospective, double-blind, randomized, placebo-controlled trial, 25 mg of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 27 publications
(48 reference statements)
1
8
0
1
Order By: Relevance
“…45 However, it was recently shown that carvedilol treatment failed to reduce restenosis after directional coronary arthrectomy in patients with coronary artery disease. 46 In that study, carvedilol was given orally 24 hours before the procedure. Such duration might not be enough for a full vascular protection of carvedilol in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…45 However, it was recently shown that carvedilol treatment failed to reduce restenosis after directional coronary arthrectomy in patients with coronary artery disease. 46 In that study, carvedilol was given orally 24 hours before the procedure. Such duration might not be enough for a full vascular protection of carvedilol in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Embora alguns pequenos ensaios tenham apresentado resultados promissores, não existem dados convincentes de que fármacos hipolipemiantes 35,36 , agentes antitrombóticos 37 , inibidores da angiotensina 38 ou betabloqueadores 39 sejam eficazes em prevenir o crescimento neointimal. Seu insucesso foi atribuído à baixa potência antiproliferativa desses agentes associada à inadequada concentração local da droga para inibir os estágios iniciais do processo de reestenose.…”
Section: Discussionunclassified
“…Although most experimental studies and some small initial clinical studies showed promise, subsequent large randomized trials have been disappointing {Faxon, 1995, Bertrand et al, 1997, Boccuzzi et al, 1998, Serruys et al, 2000. Failure to achieve significant reduction in ISR with systemic drug therapy led to the exploration of the concept of local drug delivery.…”
Section: Treatment Of Restenosismentioning
confidence: 99%